2017
DOI: 10.1007/s11130-017-0648-8
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Acrocomia aculeata Kernel Oil on Adiposity in Type 2 Diabetic Rats

Abstract: The macauba palm (Acrocomia aculeata) is native of tropical America and is found mostly in the Cerrados and Pantanal biomes. The fruits provide an oily pulp, rich in long chain fatty acids, and a kernel that encompass more than 50% of lipids rich in medium chain fatty acids (MCFA). Based on biochemical and nutritional evidences MCFA is readily catabolized and can reduce body fat accumulation. In this study, an animal model was employed to evaluate the effect of Acrocomia aculeata kernel oil (AKO) on the blood … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
20
1
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 22 publications
2
20
1
3
Order By: Relevance
“…The aqueous extract of A. aculeata (EA-Aa) is mainly composed by phenolic compounds and flavonoids, which are probably involved in the therapeutic effects of the extract. Similar data have already been described for the fruit pulp [ 23 ] and kernel of A. aculeata [ 24 , 25 , 26 ]. Plants of the same family, Arecaceae, have similar composition as EA-Aa, namely caffeic acid, rutin and quercetin [ 27 , 28 , 29 , 30 ].…”
Section: Discussionsupporting
confidence: 81%
“…The aqueous extract of A. aculeata (EA-Aa) is mainly composed by phenolic compounds and flavonoids, which are probably involved in the therapeutic effects of the extract. Similar data have already been described for the fruit pulp [ 23 ] and kernel of A. aculeata [ 24 , 25 , 26 ]. Plants of the same family, Arecaceae, have similar composition as EA-Aa, namely caffeic acid, rutin and quercetin [ 27 , 28 , 29 , 30 ].…”
Section: Discussionsupporting
confidence: 81%
“…Furthermore, Nunes et al demonstrated that experimental diabetic animals presented a reduction of glycemic levels when treated with Bocaiuva (Acrocomia sp.) oil, 39 which corroborates our results.…”
supporting
confidence: 91%
“…So, the nematode survival was improved, by the prevention of Juglone-induced oxidative damage [66]. A. aculeata fruit pulp and kernel have shown similar results, in particular the in vitro antioxidant activity and absence of cytotoxicity [67], besides hypoglycemic [68] and anti-inflammatory and diuretic effects [69].…”
mentioning
confidence: 96%